DETERMINAN KECURANGAN LAPORAN KEUANGAN (PERSPEKTIF FRAUD HEXAGON THEORY) - Rindiani Sholikatun; Makaryanawati Makaryanawati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
The purpose of this study is to determine the effect of the fraud hexagon theory on financial statement fraud. The variables used are external pressure, financial target, capability, collusion, nature of industry, rationalization, and arrogance. The population is healthcare sector companies listed on the IDX from 2016-2019. The sampling technique used purposive sampling and obtained 13 companies with 52 analysis units. The data analysis technique uses multiple linear regression. The results of this study show that variables of external pressure, financial target, capability, collusion, rationalization, and arrogance are not able to affect fraudulent financial statements. In contrast, the nature of industry variables has a negative effect on financial statement fraud. The nature of the industry, which is reflected by the ratio of changes in receivables, gives the result that the increase in receivables that occurs as a result of the increase in sales does not make the company commit fraudulent financial statements. Otherwise, the increase in receivables can be used as an opportunity to attract investors and compete with competitors. The increase in receivables does not cause the amount of cash to be reduced and is still considered sufficient for the company's operations, so the risk of fraud is lower.